Family Court Responses to Claims of Parental Alienation in Quebec. (11th August 2022) - Paquin-Boudreau, Amylie; Poitras, Karine; Bala, Nicholas
Abstract: An increasing number of cases of parental separation involve high conflict and claims that a parent is alienating a child. This study analyzes reported family law cases involving claims of parental alienation in Quebec between 2017 and 2020 (n = 164). Bivariate analyzes were undertaken to establish correlations between family characteristics (child's age, safety issues concerning the children and parents, severity of the parental conflict, child's age, allegations of domestic violence and child abuse) and court decisions. Judges made a finding of parental alienation in a minority of cases where a claim of alienation was made, and in more than a quarter of cases did not resolve the claim. Issues of family violence were raised in about a quarter of the cases where alienation was an issue. The courts rarely dismissed a claim of violence and made a finding of alienation. The most common outcome of all cases was a continuation of the status quo, with a custody reversal in only a few cases (n = 7). Mothers were more often alleged to be engaging in alienating behaviour, but there is a lower rate of judicial substantiation of alienation against mothers, and the study did not find evidence of gender bias. Judicial findings of alienation were associated with substantiation by a child custody evaluator or the child protection service. Only a small portion of cases resulted in orders psychosocial interventions. The authors argue that courts, agencies professionals need to better address issues of parental alienation and family violence.